Improving Knowledge about Snow by Crossing Qualitative and Quantitative Data from the Everest Region (Nepal) - Ornella Puschiasis; Marie Savéan; Pierre Chevallier; Joëlle Smadja; Olivia Aubriot; François Delclaux (Revue de Géographie Alpine)
In the Nepalese region of Mount Everest, snow data is fragmentary and unreliable, as in many mountainous regions of the world. To get a better understanding of solid precipitation and how it has evolved over the last decades, and thus to improve our knowledge of hydro-climatic variations, we crossed quantitative data (measured, spatialised and simulated) produced from work in hydrology, with qualitative data (field interviews) derived from work in human geography. Here we present an innovative comparison method based on three key factors: seasonality, trends and notable events. Although quantitative and qualitative data show a similar decrease in snowfall in the Upper Khumbu Valley, which is taken as a case study, there are discrepancies that highlight the uncertainties present in the two data sets. This method of crossing data from different disciplines proves very useful for mountain areas where meteorological stations and precise surveys are lacking, and where the wealth of local people’s knowledge is not sufficiently taken into account.